2012
DOI: 10.1007/s11356-012-1300-7
|View full text |Cite
|
Sign up to set email alerts
|

PAH air pollution at a Portuguese urban area: carcinogenic risks and sources identification

Abstract: O PDF relativo ao artigo que solicita, não se encontra disponível em Acesso Aberto. Motivos: O editor não permite o depósito e disponibilização em acesso aberto do PDF que solicita. Para consultar o documento deve aceder ao endereço do editor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(56 citation statements)
references
References 73 publications
3
48
1
4
Order By: Relevance
“…2. Total PAHs in aerosols of metropolitan cities around the world: a comparison of present study (∑12 PAHs) (Tokyo, Beijing, Kolkata, Hanoi and Kuala Lumpur) with previous studies (∑14 PAHs-∑17 PAHs) i.e., Madrid (Barrado et al, 2012), Kosetice (EMEP, 2010;Dvorská et al, 2012) Seoul (Park et al, 2002), Istanbul (Hanedar et al, 2014), Oporto (Slezakova et al, 2013), Sapucaia do Sul (Agudelo-Castañeda et al, 2014), Strasbourg (Morville et al, 2011).…”
Section: Seasonal Variations In Pah Concentrationsmentioning
confidence: 70%
“…2. Total PAHs in aerosols of metropolitan cities around the world: a comparison of present study (∑12 PAHs) (Tokyo, Beijing, Kolkata, Hanoi and Kuala Lumpur) with previous studies (∑14 PAHs-∑17 PAHs) i.e., Madrid (Barrado et al, 2012), Kosetice (EMEP, 2010;Dvorská et al, 2012) Seoul (Park et al, 2002), Istanbul (Hanedar et al, 2014), Oporto (Slezakova et al, 2013), Sapucaia do Sul (Agudelo-Castañeda et al, 2014), Strasbourg (Morville et al, 2011).…”
Section: Seasonal Variations In Pah Concentrationsmentioning
confidence: 70%
“…Petrogenic PAHs are usually emitted directly to a water body whereas pyrolytic are first emitted into the air (Tobiszewski and Namieśnik, 2012). The sampling site is located near urban centers being the most important PAH pollution sources, the vehicle traffic, an oil refinery and a petrochemical complex, a power plant, an incineration unit, an international shipping port and airport (Slezakova et al, 2013). The highest precipitation in the months before January may have increased the river and urban runoff of petrogenic PAHs in this period (www.ipma.pt, June, 2013).…”
Section: Pah Source Analysismentioning
confidence: 99%
“…volcanic eruptions, forest fires, oil leaks, etc.) anthropogenic sources are the main causes for PAH environmental contamination (Bucheli et al, 2004;Slezakova et al, 2013;Yunker et al, 2002). PAHs may enter the marine environment by river runoff, atmospheric inputs or wet deposition of petroleum or petroleum products (Wolska et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Sites U1 and U2 were characterized as urban and were situated in the Paranhos district of Oporto city. Previously, Slezakova et al (2011Slezakova et al ( , 2013 demonstrated that vehicular traffic emissions are the main pollution source in this area. Specifically, both sites were situated within a public garden where senior citizens gathered for social activities (i.e., board-games playing, reading, socializing in outdoor areas of coffee houses, etc.).…”
Section: Ufp Collectionmentioning
confidence: 99%
“…Prevailing winds are from west and northwest (Pereira et al, 2007). The important air pollution sources in the respective area are vehicular traffic, an international shipping port, an oil refinery and a petrochemical complex, a power plant, and an incineration unit (Slezakova et al, 2013).…”
Section: Study Area Descriptionmentioning
confidence: 99%